Egyptian Arab Spring in CNN’s Online News Reports… Supporting Peoples or Authorities is a Matter of Policy - Al- Radhi, Hanan; Pandian, Prof. Dr. Ambigapathy; Mehdi, Prof. Dr. Tengku Sepora Tengku (Journal of English Language and Literature (ISSN: 2368-2132), 2016)
This study aimed to explore Arab spring consequences that prevailed in Egypt after 2010-2011 as reflected by CNN in its online news article released in its website 2013. The main concern of the study is to unveil CNN’s hidden ideologies towards Arab spring upheaval in Egypt investigating its discoursal ’’Self’’ and ’’Other’’ representations. To achieve this goal, the researcher utilized the following theories: 1) van Dijk’s theory of Semantic Macrostructure (1980); to examine macro and micro structures of CNN’s online news articles, 2) van Dijk’s theory of Ideological Square (1998c); to examine CNN’s ideologies embedded within its online news articles and 3) Wodak’s Discourse- Historical Approach; to endorse linguistic and ideological analysis of CNN’s online news article. Fairclough’s three-dimensional Approach was utilized to organize the process of analysis. Within the linguistic analysis, macro and micro structures of CNN’s online news articles were analyzed. At the macro level, the semantic macrostructure of CNN’s text was outlined to determine its global meaning. At the micro level, the syntactic, lexical and rhetorical structures of CNN’s text were examined to determine their local meaning. Within the ideological analysis, the CNN’s online news text was analyzed to determine its ideological positive ’’Self’’ (in-group) and negative ’’Other’’ (out-group) presentations. The findings revealed that CNN’s ideological orientations towards its positive "Self" and negative "Other" were varied as far as Egyptian conflict is concerned. Thus, it presented the Egyptian new authority as the positive identities while Muslim Brotherhood as the negative "Other’’ identities.